The veil you know Individual and societal-level explanations for wearing the hijab in comparative perspective - Al-Kazi, Lubna A; González, Alessandra L. (2018)
This article examines the individual and societal explanations for the persistence of the hijab as a conservative cultural norm in persistently religious and culturally conservative communities. Analyzing data from 300 hijab-wearing women in Egypt and 198 hijab-wearing women in Kuwait, our findings confirm the importance of considering societal as well as individual-level factors in the persistence of conservative cultural norms. We find that low salience of the hijab is associated with beliefs that others misuse the hijab. High salience of the hijab is correlated with beliefs that the hijab brings its wearer greater social mobility. Exposure to non-hijab-wearers was associated with both high and low salience of the hijab, and demonstrates the influence that exposure to norm breakers has on reinforcing the salience of conservative social norms.
Keywords: Islam; Culture; Deviance; déviance; Gender; Genre; Islam; Veil; Voile